Astrobook Booklet and Its Impact on The Sixth Graders’ Scientific Literacy - Ilfiana, Aisyah Nur; Maryani, Ika (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2023)
According to the 2018 PISA research, pupils’ scientific literacy during science sessions was deficient. An effective approach to address this issue is through the utilization of printed educational materials in the form of booklets. The current study aimed to create a booklet called Astrobook as an educational tool to enhance the sixth-grade students’ scientific literacy, specifically in comprehending the solar system. We utilized a Research and Development (RD) method in conjunction with the ADDIE development model. The study instruments comprised validation sheets that were given to specialists in instructional media, content, technique, and language. We also administered surveys to educators and 19 students in the sixth grade to assess the book’s feasibility. The expert validation yielded an average score of 87.54 (highly feasible). The field trial showed a student response score of 100%. The N-Gain score, as determined by the effectiveness test, met the criteria for a medium level of effectiveness, with a mean score of 0.54. The results of this study suggest that the Astrobook booklet is effective in facilitating the learning process and enhancing students’ scientific literacy.